A report on the practice in industry training in fish preservation. - Montano, Fe A. (Manila Philippine Institute of Fisheries Techology, University of the Philippines, 1957)
The market for fish in the Philippines is greatly under supply, fish and fishery products are imported to the country consisting mostly of canned forms. Our country has all the needs of fish to most the demands of the people, but we have inadequate methods of catching and preserving them aside from the fact that the most largest and prolific banks are almost untouched. For this reason the government has in later years gave more attention towards the development of the fishing industry. With a thorough combine efforts some measures were attained and laws were enacted to utilize our marine resources. The Philippine institute of fisheries technology was opened for the students to teach on the specific methods of conserving and protecting fish life and other marine resources. As a requirement for graduation we are obliged to have a period of six months practical training. These periods of time I have learned much on the practical side and the knowledge I have gained from the classrooms are applied.
Report
Keywords: Fish-Preservation.